Opportunities and Challenges for Local Food in the International Market from the Perspective of Sharia Economics - Nurintan Siregar; M. Kamal Hadi; Hamonangan (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Introduction: Local food products have significant potential to be developed as competitive commodities in the international market, in line with the increasing global demand for authentic, ethical, and culturally based food products. From the perspective of Islamic economics, local foods are highly relevant as they generally comply with the principles of halal and thayyib. Methods:This study aims to analyze the opportunities and challenges of developing local food products in the international market from an Islamic economic perspective. The research employs a qualitative descriptive approach using a library research method. Data were collected from academic books and scholarly journal articles and analyzed through content analysis techniques. Results:The findings indicate that local food products have strong opportunities in the global market due to their cultural uniqueness, compliance with halal and thayyib principles, and the support of digital marketing and globalization. However, their development still faces several challenges, including limitations in product standardization, international halal certification, global trade regulations, as well as weak innovation and branding strategies. Conclusion and suggestion: This study concludes that the development of local food products based on Islamic economics requires integrative strategies that strengthen halal and thayyib standards, enhance product innovation and value-based branding, and are supported by sustainable policies to improve competitiveness and contribute to the empowerment of the Muslim economy in global trade.